Os caminhos da formulação de políticas públicas da Scotland’s LGBT Inclusive Education - Mannaro, Patrícia da Silva Rosa (2022)
This paper aims to study the unfriendly school environment focus on the issues that many children and young people are inserted because of lgbtphobic bullying and the trouble of developing a school curriculum that dialogue with differences and encourages pedagogical practices capable of breaking the compulsory heteronormativity, dominant culture, and gender identities inside the school. Trying to understand possible options, this research studies construction of LGBT educational public policies in Scotland, whose planned implementation for March 2021 in all Scottish schools, based on the Scottish Equality Act of 2010 and the Scottish Curriculum for Excellence (CfE). In this context, the development of public policies of Scotland’s LGBT Inclusive Education was inserted mainly in the Scottish Executive Education Department (SEED) with the support of the Scottish Executive Health Department (SEHD), considering that the theme is included in the Curriculum for Excellence (CfE) in health and well-being. Thus, as the main goal, it was considered the methods and approaches that promoted the formulation of LGBT educational public policies Scotland's, capable of inserting the LGBT into the Curriculum for Excellence (CfE). Secondarily, it was investigated the Scotland governmental motivations to consider the 33 Recommendations from the Time for Inclusive Education (TIE) Campaign 2015 and the possible social impacts. This research carried out from 2019 to 2021, it had the theorical base of this studied the Post-Critical curriculum theory, the methodology was documentation analysis guided by the 33 Recommendations from LGBT Inclusive Education, done by the LGBTI Inclusive Education Working Group, created by the Scottish government, the analysis of many government and parliament documents and laws, children and young people mental health researches, lgbtphobic bullying at the schools, sexual education documents, Inclusive Education public policies formulation and data collection from Scottish government representatives, Civil society and schools. The search sources of information were official parliament and the government sites, Scotland political party sites, international Human rights non-governmental organizations, Scottish civil society, academics sites, virtual libraries, and scientific magazines. The research was structured with 3 chapters, the first was based on theoretical foundations, the second one presents the information before Scotland’s LGBT Inclusive Education, the third one about is the public policies formulation that created the LGBT Inclusive Education and the possible social tensions around this. Against the documentation analyzed, that had an important progress in the reformulation of the school curriculum is not possible to claim that it will have effective impacts on the pedagogical practices trying to promote equality and isonomy, it will depend on the development in the implementation phase. Besides that, strongly questioned, the term “inclusion” strengthens social exclusion. Further, the LGBT theme was inserted in the Curriculum for Excellence (CfE) based on the binary identities structure. Finally, Scotland’s LGBT Inclusive Education does not present any justification of excluding identities or selecting which will be socially accepted, and the deep criticism about the limitation of the LGBT acronym